THEOLOGIES OF RELIGION AND THEOLOGIES OF LIBERATION: A SEARCH FOR RELATIONSHIP - Samartha, S J (Journal of Dharma, 1996)
We meet at a time when momentous changes are taking place in the world. In western Europe, in spite of their attachment to national identities, people seek to come together as a European community. In eastern Europe, on the other hand, with the weaken. ing of Marxist ideology, there is a disintegration of socialist states and the emergence of ethnic, linguistic and religious plurality.